IMPROVED ANALYTICAL METHOD FOR ESTIMATION OF ESSENTIAL OIL IN DRUG OINTMENT THROUGH RAPID STATIC CHROMATOGRAPHY HEADSPACE FOR QUALITY CONTROL ANALYSIS - Nk, Dhir; M, Joshi; V, Kaur (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective for new methodology was to develop a rapid analytical method for drug quantification in ointment samples and eliminate the usage of hazardous solvents in the sample and standard preparation, less elution time of component of interest to sustained green chemistry applications. Methods: Headspace (HS) chromatography was used along with gas chromatography (GC) having direct sample treatment with the help of calibration slope method. Results: All essential oil (EO) was well separated from each other and eluted 1.6 times faster from traditional classical GC method. The present method does not require any hazardous solvents for sample preparation. Conclusion: This method provides the accurate and precise results for EO added in ointment samples and can be used for routine quality control testing before releasing the final product release for the consumers.